SIKAP CARA BELAJAR DAN PRESTASI BELAJAR - Maman Maman (Faktor Jurnal Ilmiah Kependidikan, 2018)
Abstract; This study aims to determine the Influence of Attitudes and Learning Method pesrta students (students) On Achievement Learning. The method used is a survey with correlation and regression analysis techniques to determine the effect between each variable, The sample used as the object of research are the students who collected and then analyzed descriptive statistics and test data analysis requirements before hypothesis testing. While the secondary data obtained from the school documentation that is the value of Deuteronomy Semester (UTS). From the results of data analysis and hypothesis testing obtained the conclusion that: (1) There is a significant influence of attitudes and ways of learning together towards the achievement of learning History of high school students in District Cibinong Bogor Regency. This is evidenced by the sig value. 0,000 <0.05 and F arithmetic = 18.205. (2) There is a significant influence Attitude on learning achievement History of Negari Senior High School students in Cibinong District, Bogor Regency. This is evidenced by the sig value. 0,023 <0,05 and t count = 2,340. (3) There is a significant influence of the way of learning on learning achievement History of SMA Negeri students in District Cibinong Bogor Regency. This is evidenced by the sig value. 0,011 <0,05 and t count = 2,632. Keywords: Attitude, Learning Method, Learning Achievement